Analysis of Zoning System Implementation Policies in The Admission of New Students of Junior High School in Sukabumi City - R. Niske Dewintania; Ike Rachmawati; Unin Nibi Saputra; Alhidayatullah (PT Inovasi Pratama Internasional, 2023)
The admission of the new students (PPDB) zoning system start to be enforced in Indonesia through the Regulation of the Minister of Education and Culture (Permendikbud) No. 17 of 2017. This policy applies to all City and Regency Education Offices in Indonesia. The policy applies in Sukabumi City in 2018 due to the readiness of human resources, infrastructure, and financial resources owned by Sukabumi City. The purpose of this study is to find out how the implementation of the zoning system policy in accepting new students, as well as the inhibiting factors in achieving the objectives of the new student admission policy in junior high schools in Sukabumi City. The research was conducted to analyze the implementation of the PPDB zoning system in Sukabumi City using qualitative methods with the analysis technique of the Miles and Huberman models to compare with the theory originating from Van Meter and Van Horn. The results showed that Sukabumi City had implemented a zoning system to the variables in the Van Meter and Van Horn theories. There are several goals had not been achieved, namely removing the favorite school label, reducing dropout rates, increasing the net enrollment rate index, bringing parents and children closer together, and evaluating the distribution of schools in Sukabumi City. The goal has not been achieved because of the lack of bureaucratic commitment and fragmentation in the form of pressure from outside the bureaucratic unit.